2016
DOI: 10.1182/asheducation-2016.1.683
|View full text |Cite
|
Sign up to set email alerts
|

New treatment approaches to von Willebrand disease

Abstract: von Willebrand disease (VWD) is the commonest inherited bleeding disorder and results from either a quantitative or qualitative deficiency in the plasma glycoprotein von Willebrand factor (VWF). Recent large cohort studies have significantly enhanced our understanding of the molecular mechanisms involved in the pathogenesis of VWD. In contrast, however, there have been relatively few advances in the therapeutic options available for the treatment of bleeding in patients with VWD. Established treatment options … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 42 publications
(60 reference statements)
0
44
0
2
Order By: Relevance
“…Collectively, these observations have led to concerns that the clinical efficacy of DDAVP administered at 12–24 hourly intervals may be attenuated in VWD patients with enhanced VWF clearance. Consequently, VWF‐containing concentrates may represent a longer‐lasting and more efficacious therapeutic option for these patients, particularly in the context of surgery or major bleeding complications (Lavin & O'Donnell, ). Critically, studies to date have shown that the half‐life of infused plasma‐derived VWF concentrates in type 1C patients is normal, suggesting that the enhanced clearance phenotype observed in most cases is primarily attributable to changes in the endogenous VWF molecule (e.g.…”
Section: Management Of Vwd Patients With Enhanced Clearancementioning
confidence: 99%
“…Collectively, these observations have led to concerns that the clinical efficacy of DDAVP administered at 12–24 hourly intervals may be attenuated in VWD patients with enhanced VWF clearance. Consequently, VWF‐containing concentrates may represent a longer‐lasting and more efficacious therapeutic option for these patients, particularly in the context of surgery or major bleeding complications (Lavin & O'Donnell, ). Critically, studies to date have shown that the half‐life of infused plasma‐derived VWF concentrates in type 1C patients is normal, suggesting that the enhanced clearance phenotype observed in most cases is primarily attributable to changes in the endogenous VWF molecule (e.g.…”
Section: Management Of Vwd Patients With Enhanced Clearancementioning
confidence: 99%
“…Asimismo, la optimización del tratamiento a largo plazo de estos pacientes demanda la conducción de ensayos clínicos, con el objetivo de ofrecer mejor evidencia que permita tomar decisiones clínicas acertadas. Por otro lado, los avances en ingeniería genética resultan prometedores para proveer una terapia genética dirigida a pacientes con EVW (67).…”
Section: Discussionunclassified
“…Adicionalmente, deben tenerse en cuenta las recomendaciones para procedimientos quirúrgicos: cirugía menor, niveles de FVW:RCo ≥ 50 UI/dL el día del procedimiento y el primer día postoperatorio, y > 30 UI/dL 2 a 5 días postoperatorio, o hasta la caída de la escara. Cirugía mayor, los niveles de FVW:RCo deben ser 100 UI/dL el día del procedimiento y durante el primer día postoperatorio, y deben mantenerse ≥ 50 UI/dL de 7 a 14 días o hasta la cicatrización completa (67).…”
Section: Tratamientounclassified
“…These VWF concentrates differ in several aspects, including source of plasma, purification methodology, viral inactivation steps, and FVIII content (recently reviewed by Lavin and O'Donnell). 51 In addition, a first recombinant VWF concentrate has recently been developed and licensed for use in some countries. 36…”
Section: Treatment Options For Patients With Low Vwfmentioning
confidence: 99%